Testosterone Is High among Young Black Men with Little Education - Mazur, Allan (Frontiers in Sociology, 2016)
Participation in the “honor culture” of poor black inner cities puts young men on constant alert for challenges to their reputations. Hypothetically, this vigilance raises their testosterone (T), which in turn facilitates dominant contests that may end violently. One prior study reports the predicted hormonal pattern including higher T among young black men with low education, compared to young white men with low education, but no race difference in T between young men who are better educated or in older men (Mazur 1995). However an attempt to find this pattern on another large sample failed to do so (Mazur 2009). The present results, using the HANES 2011-2012 data set, do replicate the predicted pattern among men. The pattern is not seen among teenage boys or among females.